China and India pre-1939 - Wagner, Rudolf G. (Routledge handbook of China-India relations, 2020)
The chapter questions the historiography of the India-China relationship based on the Hindi Chini bhai bhai (Indians and Chinese are brothers) narrative from the early 1950s. It addresses three issues: first, what are the changes in the mutual perception and appreciation of “India” and “China” since the first recorded contacts. Second, who were the principle agents operating the relationship. Third, what role did India play in the Chinese discussion about regaining Chinese sovereignty since the 1890s. It concludes that there was marginal mutual interest on both sides in the other notwithstanding the evident importance of Buddhism. China moved from viewing India as the holy land to sanctifying its own territory. The main agents in the India-China interaction were neither Indians nor Chinese but rather Arabs and Sogdians and other Central Asians. In the Chinese sovereignty discussions, India played the role of a failed state. Responsible for India’s failure was weakness of the Indian character rather than overpowering outside forces. Eventually, the claim was made that the perceived weak response of the Chinese populace to Japan’s aggression was due to the “Indianization of China” through Buddhism. The Indian and Chinese discussions about the other are in fact about themselves.
Gesehen am 24.04.2023